Conhecimento dos adolescentes sobre métodos contraceptivos: pesquisa-ação em uma unidade do programa saúde da família de Natal - Torres, Sandra Maria da Solidade Gomes Simões de Oliveira (2008)
It is a descriptive study with a qualitative approach, and an action-research type, which aimed to analyze the changes of knowledge about contraceptive methods invested to a teenager group attended in Igapó Family Healthcare Unit, in the city of Natal/RN, after consent and institutional assent of Ethics Committee of Rio Grande do Norte Federal University (Protocol No. 131/07). It were researched 16 teenagers of both sexes, with age ranging from 11 to 16 years. We used two structured questionnaires, one in the initial diagnosis and another during the seven meetings of the focus group, in addition to the field notes and the meetings discussions transcriptions. The data-collection was performed in the period of two months by a team composed by a nurse the research coordinator, a dentist, a nursing assistant, a community-based healthcare worker and a nursing academic. The quantitative and qualitative data were organized, tagged and categorized into spreadsheet in Microsoft Excel, being held a thematic analysis of speeches performed by the study participants. The results were presented as tables, graphics, photos, drawings and word clippings. The educational strategy developed in focus group allowed adolescents to discuss, exchange ideas and opinions on several contraceptive methods, providing expansion in knowledge of all contraceptives discussed, especially those natural and surgical, which were less mentioned at the beginning of the study. Among the advantages of the contraceptive methods listed by teenagers, was highlighted avoiding pregnancy and STDs in use of the barrier method of condom. As for the disadvantages more frequently noted by the survey with the misuse of barrier methods, was highlighted get pregnant, acquire STD's and do not prevent STD's in hormonal, natural and surgical methods. Adolescents showed consistency between the advantages and disadvantages and types of contraceptive methods, showing a widening in knowledge among them. It may be said that, in general, those surveyed had a good understanding about the use of the various contraceptive methods. Thus, the study participants had positively evaluated all the criteria used to qualify the meetings in the focus group. The action strategy of the focus group should be encouraged by professionals who work with teenagers, since they prefer to live in groups, one characteristic of adolescence.